Analisis Keandalan Mesin Milling CNC Menggunakan Metode Failure Mode and Effect Analysis - Nina Hardiyanti; Mokhammad Munir Fahmi; Edward Simanjuntak (BULLET : Jurnal Multidisiplin Ilmu, 2025)
Machine reliability in production units is an important aspect in ensuring productivity and efficiency in various industrial sectors. The purpose of this study is to focus on improving reliability. The Failure Mode and Effect Analysis (FMEA) method is used to analyze as an effort to improve machine reliability. FMEA provides a comprehensive understanding of reliability improvement strategies by strengthening reliability prediction and preventive maintenance strategies. This method is also used to identify potential failures in the system, evaluate their impact, and design effective maintenance strategies. Results and Discussion showed that the Mazak Variaxis CNC milling machine had the highest percentage of problems, reaching 40% based on downtime and frequency of occurrence in the prismatic cell. Based on the FMEA analysis, the main failure mode was identified through the calculation of the Risk Priority Number (RPN) with the highest values ​​of 126 (rank 1), 120 (rank 2), and 105 (rank 3). RPN values ​​greater than 87.93 are categorized as critical failures. The ATC (Automatic Tool Changer) component occupies a crucial position with the highest percentage of component problem factors, reaching 129%. Conclusion: By using an empirical approach, the proposed implementation of actions as an effort to reduce the RPN number and increase machine reliability by prioritizing problems based on the RPN value scale, increasing the intensity of preventive maintenance scheduling and periodic replacements, and planning spare parts stock.